Atypická lokalizace pyoderma gangraenosum u nemocného s ulcerózní kolitidou - Husová, L; Husa, P; Berger, R; Feit, J; Hauerová, V; Parízková, R; Kroupa, R (Vnitrni lekarstvi, 2005)
The authors present a case of 61-year-old man with ulcerative colitis and with extraintestinal manifestation of the disease in the form of pyoderma gangraenosum. Multiple skin defects, which developed in atypical localisation (extensive affection of facial and hairy parts of the head) in patient with chronically active form of ulcerative colitis were complicated with bacterial contamination of methicilin-resistant strains of Staphylococcus aureus. After application of the parenteral feeding, corticotherapy and targeted antibiotic therapy the subjective and objective status of the patient markedly improved, stool frequency was reduced, admixture of blood in the stool disappeared, temperatures fell back and there was a decrease in activity of non-specific bowel inflammation in laboratory findings. However endoscopic examination of the intestine confirmed the finding of chronically active ulcerative colitis with ulcerations and bridging polyps. Patient was indicated to total colectomy, but he refused it.
Keywords: Scalp Dermatoses; ulcerózní kolitida; dermatózy skalpu; Middle Aged; mužské pohlaví; Humans; Facial Dermatoses; Pyoderma Gangrenosum; obličejové dermatózy; Colitis, Ulcerative; pyoderma gangrenosum; lidé; Male; lidé středního věku